2009
DOI: 10.1111/j.1753-0407.2009.00013.x
|View full text |Cite
|
Sign up to set email alerts
|

Mild and severe forms of tuberculosis in diabetic and non‐diabetic patients

Abstract: Background:  The aim of the present study was to compare the frequency of pleural tuberculosis in patients with and without diabetes mellitus (DM). Methods:  Three hundred consecutive patients who were smear positive for pulmonary tuberculosis or isolated pleural tuberculosis were enrolled in the study. Patients’ age and smoking status (pack‐years) were recorded. Patients were divided into two groups: those with and without DM. Results:  All patients enrolled in the study were male. Mean (±SD) patient age was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0
7

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 15 publications
3
6
0
7
Order By: Relevance
“…However, there were other studies that showed a higher incidence of lower lobe involvement among DM TB cases [52-54]. Also, there was no significant difference in the frequency of pleural effusions or isolated pleural TB between patients with and without DM [44,50]. …”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…However, there were other studies that showed a higher incidence of lower lobe involvement among DM TB cases [52-54]. Also, there was no significant difference in the frequency of pleural effusions or isolated pleural TB between patients with and without DM [44,50]. …”
Section: Introductionmentioning
confidence: 89%
“…Furthermore, one study showed an association between lower lung field involvement and female gender or age greater than 40 years [47]. Also, it has been suggested that severe pulmonary involvement in DM patients may actually be related to smoking status and not DM alone [50]. …”
Section: Introductionmentioning
confidence: 99%
“…Registrovan je manjak volumena plućne kapilarne mreže, zbog zahvaćenosti pluća dijabetesnom mikroangiopatijom, što dovodi do poremećenog odnosa ventilacije i perfuzije na štetu perfuzije u donjim režnjevima, porasta alveolarnog parcijalnog pritiska kiseonika, što pogoduje boljoj reprodukciji aerogenog Mycobacteriuma tuberculosis [11]. U literaturi postoji više studija koje nisu našle ni na kakvu razliku u radiografskoj distribuciji tuberkuloze kod pacijenata sa dijabetesom i bez dijabetesa, i odgovaraju i rezultatima naše studije [12,13]. Međutim, postoje i studije koje su pokazale atipičnu lokalizaciju tuberkuloze kod dijabetičara sa većom incidencom zahvatanja donjih režnjeva pluća [14,15].…”
Section: Diskusijaunclassified
“…Moreover, there exist recurrent factors of risk like age, stress, undernourishment, alcoholism, cancer, smoking (Semba et al, 2010), and recurrent infections that can cause the resistance, being in the reactivation of the LTBI and the development of the disease (Bouchonnet et al, 2002). Relative risk factors for developing active TB are silicosis, diabetes mellitus (Ocal et al, 2009), chronic renal failure and hemodialysis, gastrectomy, jujenoileal bypass, renal and cardiac transplant and carcinoma of head and neck. Malnutrition markedly increases mortality among both TB and HIV/AIDS patients (Semba et al, 2010), HIV infection and malnutrition lower immunity, increases the risk of reactivation of TB and primary progressive disease.…”
Section: Introductionmentioning
confidence: 99%